Air quality, Environment and Respiratory Outcomes in Bronchopulmonary Dysplasia, the AERO-BPD cohort study: design and adaptation during the SARS-CoV-2 pandemic. Issue 1 (30th June 2021) - Ruran, Hana B; Adamkiewicz, Gary; Cunningham, Amparito; Petty, Carter R; Greco, Kimberly F; Gunnlaugsson, Sigfus; Stamatiadis, Natalie; Sierra, Gabriella; Vallarino, Jose; Alvarez, Marty; Hayden, Lystra P; Sheils, Catherine A; et al.
Abstract : Introduction: Almost half of all school-age children with bronchopulmonary dysplasia (BPD) have asthma-like symptoms and more suffer from lung function deficits. While air pollution and indoor respiratory irritants are known to affect high-risk populations of children, few studies have objectively evaluated environmental contributions to long-term respiratory morbidity in this population. This study aimed to examine the role of indoor environmental exposures on respiratory morbidity in children with BPD. Methods and analysis: The Air quality, Environment and Respiratory Ouctomes in BPD (AERO-BPD) study is a prospective, single-centre observational study that will enrol a unique cohort of 240 children with BPD and carefully characterise participants and their indoor home environmental exposures. Measures of indoor air quality constituents will assess the relationship of nitrogen dioxide (NO2 ), particulate matter (PM2.5 ), nitric oxide (NO), temperature and humidity, as well as dust concentrations of allergens, with concurrently measured respiratory symptoms and lung function. Adaptations to the research protocol due to the SARS-CoV-2 pandemic included remote home environment and participant assessments. Ethics and dissemination: Study protocol was approved by the Boston Children's Hospital Committee on Clinical Investigation. Dissemination will be in the form of peer-reviewed publications and participant information products. Trial registration number: NCT04107701 .